The Students’ Perceived Effectiveness of TikTok as A Means for Learning Unfamiliar Vocabulary at SMAN 10 Mataram - Hartomo, Lalu Marlin; Waluyo, Untung; Putera, Lalu Jaswadi; Soepriyanti, Henny (Jurnal Ilmiah Profesi Pendidikan, 2024)
This study examines the perceived effectiveness of TikTok as a tool for learning unfamiliar vocabulary among students at SMAN 10 Mataram. With the rise of social media, TikTok has emerged as a popular platform for educational content, prompting educators to explore its potential in language learning. Through surveys and interviews, this research investigates how TikTok influences vocabulary acquisition, engagement, and motivation in learning. The findings suggest that students view TikTok as an effective and engaging resource that enhances their vocabulary learning experience. The study highlights implications for incorporating social media into educational practices and offers recommendations for leveraging TikTok in language education.